2015
DOI: 10.1016/j.ypmed.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Providers' knowledge, attitudes, and practices related to colorectal cancer control in Brazil

Abstract: In Brazil, colorectal cancer (CRC) is the fourth most common cause of cancer-related death among men, and the third most common among women. We aimed to examine CRC screening-related knowledge, attitudes, and practices among physicians and nurses working in Brazil’s network of health units, and to describe the capacity of these units for CRC screening. In 2011, 1600 health units were randomly selected from all 26 states and the Federal District. One coordinator and one health care provider were selected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Since the subjects were studying Bachelor of Science in nursing and midwifery, and once had passed the specific courses of physical activity education, the average of their knowledge and attitude was in high level. Some studies observed a positive relationship between knowledge regarding physical activity and literacy level (9)(10)(11). Literacy level had a positive relationship with subjects' attitude towards physical activity (5, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Since the subjects were studying Bachelor of Science in nursing and midwifery, and once had passed the specific courses of physical activity education, the average of their knowledge and attitude was in high level. Some studies observed a positive relationship between knowledge regarding physical activity and literacy level (9)(10)(11). Literacy level had a positive relationship with subjects' attitude towards physical activity (5, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in diagnosis and treatment, mortality rates remain high due to the lack of government investments to create programs for the early detection of disease in developing countries, such as Brazil, and intrinsic characteristics such as tumor resistance to conventional chemotherapy and side effects. Due to these factors, the search for new compounds with anticancer activity is of extreme importance [15].…”
Section: Discussionmentioning
confidence: 99%
“…The patients in this study had an overall survival of 53.3%, indicating the still late diagnosis of these tumors and the lack of more effective screening programs in the country. In Brazil, although the public health system offers comprehensive primary health care services, the country does not have a national government policy or program addressing CRC prevention and control [103]. Unfortunately, there is still much to be discussed about CRC screening and prevention strategies in the country.…”
Section: Plos Onementioning
confidence: 99%